Electrochemical behavior of active surface layers in AA8xxx aluminum alloys. (11th February 2019) - Andreatta, Francesco; Lanzutti, Alex; Maschio, Stefano; Fedrizzi, Lorenzo
Abstract : AA8xxx alloys employed in the HVAC&R sector (heating, ventilating, air conditioning, and refrigerating) were investigated to highlight the effect of active surface layers in heat‐exchanger fins. The local behavior of the surface and the bulk of the alloy sheets was studied by means of an electrochemical microcell in combination with glow‐discharge optical‐emission spectrometry. Surface layers strongly enhance the electrochemical activity of the fin material. This is related to the segregation of Mg and other elements (Sn) strongly impairing the protective behavior of the oxide film generated during thermomechanical processing.